The impact of employing the technology of enhanced reality in the development of higher thinking skills among middle school students - Al - Zahrani, Haifa ali (Journal of Educational and Psychological Sciences, 2018)
The aim of the study was to find out the impact of the employment of the technology of enhanced reality in the development of the skills of the high level of infidelity among the students of the intermediate stage. The researcher used the descriptive method to describe the phenomenon, and used the questionnaire as a tool of study to collect data, and the sample of the study was 135 teachers of the intermediate stage in the Kingdom, The use of technology enhanced reality technology leads to a great interaction between students in the educational process.1- The use of technology technologies enhanced during the educational process increases the motivation of students in learning and inform students happy when using these techniques in the explanation, resulting in greater interaction of the student and the textbook, which has an impact in the retention of information for longer periods.2- The difficulty of providing large numbers of devices that support the enhanced reality technologies in the Kingdom's schools.
Keywords: Augmented reality technology; higher-order thinking skills; middle school; education